Extraction and separation of parabens in aqueous biphasic systems / Noorashikin Binti Md Saleh - Noorashikin, Md Saleh (2014)
In this study, five systems for extraction of parabens were developed, namely ionic liquid based aqueous two-phase system (IL-ATPS), ionic liquid based aqueous two-phase system with β-cyclodextrin (IL-βCD-ATPS), cloud point extraction (CPE-DC193C), cloud point extraction with β-cyclodextrin (CPE-DC193C-βCD) and cloud point extraction with β-cyclodextrin-ionic liquid (CPE-DC193C-βCD-IL). These five developed methods have been optimized in order to get the optimum conditions for phase separation of parabens in water samples. These new, green, fast and simple extraction techniques coupled with a reversed-phase high performance liquid chromatography (RP-HPLC) showed excellent results for extracting parabens from aqueous samples. β-CD and βCD-IL as modifiers improved the sensitivity of IL-ATPS and CPE-DC193C systems. The experimental results demonstrated that the method detection limits (LOD) for studied parabens using IL-βCD-ATPS were in the range of 0.022-0.075 μgmL-1 and CPE-DC193C-βCD-IL methods were in the range of 0.013-0.038 μgmL-1. These LOD results were relatively lower compared with IL-ATPS, CPE-DC193C and CPE-DC193C-βCD methods. Addition of β-CD and βCD-IL as modifiers also improved the selectivity of the developed methods. The use of IL-βCD-ATPS reduced the matrix effect and hence, percentage of recovery of parabens extraction increased from 88.0-92.8% to 96.0-98.5%. The recoveries of parabens extraction in sea water using IL-ATPS were dramatically improved with addition of β-CD in the IL-βCD-ATPS method. The mixture of βCD-IL with the surfactant molecules and parabens in the formation of micelles produced the extra large complex formations during the CPE process. The CPE-DC193C-βCD-IL system offered an obviously lower phase volume ratio compared to CPE-DC193C-βCD and CPE-DC193C systems with the value of phase volume ratios as 0.74, 0.92 and 1.63 respectively at 30% (w/v) surfactant concentration. On the other hand, IL-βCD-ATPS system also showed a lower phase volume ratio with the value of 0.16 compared to 0.19 for IL-ATPS at 30% (w/v) ionic liquid concentration. The developed method of CPE-DC193C-βCD-IL showed the highest preconcentration factor with the values for MeP (methyl paraben), EtP (ethyl paraben), PrP (propyl paraben) and ArP (benzyl paraben) were 76, 89, 97 and 110, respectively. While, the highest preconcentration factors for IL-βCD-ATPS were 70, 86, 95 and 103 for MeP, EtP, PrP and ArP respectively. When the surfactant concentration was increased from 5% (w/v) to 60% (w/v), ArP in CPE-DC193C-βCD-IL method the measured total loss of water content was 68%. ArP lost about 50 % (w/v) water content v in IL-βCD-ATPS compared to IL-ATPS where ArP lost only 43 % (w/v) water content when the ionic liquid concentration increased. It shows that CPE-DC193C-βCD-IL is considered as the highest loss of water content compared to the CPE-DC193C-βCD, CPE-DC193C, IL-βCD-ATPS and IL-ATPS systems. The overall loss of water content for MeP was 55%, followed by EtP and PrP with 52% each in CPE-DC193C-βCD-IL. Moreover, the distribution coefficient of parabens in surfactant-rich and ionic liquid rich phase in the order of hydrophobicity of parabens is MeP<Etp<PrP<ArP. In conclusion, βCD-IL contributes to a higher distribution of parabens in surfactant-rich phase compared to the other methods.